A Counseling Program for Clients in Substitution Treatment: Effects and Dropout Prediction. (16th October 2012) - Boywitt, C. Dennis; Zwingmann, Christian
Abstract : The present research reports the evaluation of a counseling program for substance abusers in outpatient substitution treatment. Clients were assessed at two time points to evaluate their development on various variables such as psychosocial functioning and substance abuse. Importantly, central outcome variables were assessed via self-reports and ratings by the primary counselor. Methodologically, the challenge was to estimate program impact without a control group as by German law any client in outpatient substitution treatment must be provided with psychosocial counseling. While results suggest that the program positively influences psychosocial functioning, the level of substance abuse did not significantly decrease during the course of the study ( N = 101). Furthermore, because program dropout is a major problem in interventions for substance abusers, logistic regression analysis was employed to identify relevant preconditions which predict future program dropout ( N = 172). Although several significant predictors were identified, they only provide a modest increase in prediction performance.